Differentiated Literacy Modules Based on Student Interests: Enhancing Procedural Writing in Indonesian Primary Schools - Narsita, Ingelin; Wagiran; Sri Wardani; Lailatul Mukaromah (Global Action and Education for Society, 2025)
This study aims to develop and evaluate differentiated literacy modules based on student interests to enhance procedural writing skills among fifth-grade students in Indonesian primary schools. In alignment with the Merdeka Curriculum, the modules were created using the 4D development model (Define, Design, Develop, Disseminate). Each module was designed to accommodate individual learning preferences, including visual, auditory, and kinesthetic styles, and was enriched with diagnostic assessments of student interests and readiness. The content addressed four key language components: reading, listening, writing, and speaking, supported by multimedia features such as QR codes linked to videos and audio recordings. Expert validation indicated that the modules were highly feasible, with ratings ranging from 75 percent to 100 percent across media, content, and language aspects. Initial small-scale testing revealed minimal improvement in student outcomes, with a mean score increase of only 0.667 points and an N-Gain of 1.67 percent. Following revisions, a large-scale trial involving 27 students demonstrated significant effectiveness. The posttest mean rose to 80.93 from 47.78, with a statistically significant result (t = 27.671, Sig. = 0.000) and an average N-Gain of 63.75 percent. These findings confirm that interest-based differentiated instruction can effectively improve student achievement in procedural writing and offers a scalable model for inclusive literacy development in primary education.